ЗМЕНШЕННЯ ВПЛИВУ ВІДХИЛЕНЬ ПАРАМЕТРІВ ГЕНЕРАТОРІВ У ПРЕЦИЗІЙНИХ КВАДРАТУРНИХ МОСТАХ - Борщев, П.І.; Ламеко, О.Л.; Мельник, В.Г. (Інститут електродинаміки НАН України, Київ, 2024)
The article is devoted to solving the problem of attestation of electric capacity standards at industrial frequency. The expediency of using a quadrature bridge of alternating current to determine the parameters of standards of electric capacity at industrial frequency by comparison with the parameters of standards of active resistance was noted. The advantage of using a bridge imbalance indicator with high input impedance is shown, which consists in the possibility of reducing the influence of higher harmonics of the supply voltages. An analysis of the well-known method of reducing of measurement errors caused by the deviation of the generator parameters from the calculated ones was carried out. It is shown that the known method does not provide sufficient compensation for the influence of these errors when the deviations of the generator parameters increase, as well as when the deviations of the bridge from the balance state increase. An iterative algorithm for calculating the measured deviation of the impedance ratio of the compared standards from the nominal value is proposed. Mathematical expressions for calculating the measured quantity are given. Calculations of the components of the measurement error for different values of generator voltage deviations were carried out. Calculations were performed for two variants of generator voltage variation implementation: multiplicative voltage amplitude variation and additive voltage phase variation. The developed iterative correction method allows to reduce the specified errors to the required levels in a small number of iteration steps - in the vast majority of cases, two steps are enough. The application of the method allows obtaining high metrological characteristics with rather large deviations of the voltage ratio of bridge generators, which makes it possible to reduce hardware costs when implementing quadrature alternating current bridges for comparing capacitance and active resistance standards. References 18, figure 1, table 1.